Oral calcium carbonate affects calcium but not phosphorus balance in stage 3–4 chronic kidney disease - Hill, Kathleen M. (2012)
Chronic kidney disease (CKD) patients are given calcium carbonate to bind dietary phosphorus and reduce phosphorus retention, and to prevent negative calcium balance. Data are limited on calcium and phosphorus balance in CKD to support this. The aim of this study was to determine calcium and phosphorus balance and calcium kinetics with and without calcium carbonate in CKD patients. Eight stage 3/4 CKD patients, eGFR 36 mL/min, participated in two 3-week balances in a randomized placebo-controlled cross-over study of calcium carbonate (1500 mg/d calcium). Calcium and phosphorus balance were determined on a controlled diet. Oral and intravenous 45calcium with blood sampling and urine and fecal collections were used for calcium kinetics. Fasting blood and urine were collected at baseline and end of each week of each balance period for biochemical analyses. Results showed that patients were in neutral calcium and phosphorus balance while on placebo. Calcium carbonate produced positive calcium balance, did not affect phosphorus balance, and produced only a modest reduction in urine phosphorus excretion compared with placebo. Calcium kinetics demonstrated positive net bone balance but less than overall calcium balance suggesting tissue deposition. Fasting biochemistries of calcium and phosphate homeostasis were unaffected by calcium carbonate. If they can be extrapolated to effects of chronic therapy, these data caution against the use of calcium carbonate as a phosphate binder.